Implementasi REST API Pengelolaan Data Penduduk Multi-Desa Berbasis Laravel dengan Autentikasi Sanctum - Aldino Dewa Ndaru; Mujahidin Aljawari; Muh Yudha Setiawan (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2025)
Village websites currently generally only provide information in the form of an interface for users, such as village profiles, potential areas, population data, and current news. However, the majority are not yet equipped with Application Programming Interface (API) support that allows for flexible and automated data integration and exchange. This is a challenge when dynamic access is needed by third-party systems, such as public service platforms, mobile applications, or local government information systems, which require real-time and accurate synchronization of population data. The project aims to implement a RESTful API that can be accessed securely, efficiently, and easily understood by developers to retrieve villagers' data. The development of the system is carried out using the Agile method, which supports rapid iteration and periodic evaluation to ensure that each feature functions optimally according to the needs of users and field conditions. This Agile method is applied in several sprints that include the stages of needs planning, designing the API endpoint structure, coding, documentation, and testing of the integration and security of the system as a whole. The results of the implementation show that the API successfully retrieves data directly from the village database, and presents it in a JSON format that is compatible for use by both frontend and third-party systems. This API supports pagination features for efficient access to large amounts of data, and is equipped with Basic Authentication to keep data access secure from being abused. With this API, the village website not only becomes a static information medium, but also transforms into a digital service platform that is open for cross-system integration. This supports the development of a more modern, efficient, sustainable, and collaborative village information system in the future, so that public services can be significantly improved.